Multilevel secure access control policy for distributed systems - Ming-xin MA; Guo-zhen SHI; Ya-qiong WANG; Hao-jie WANG; Wen-wen CHENG (网络与信息安全学报)
A multilevel secure access control strategy for distributed system was proposed,which could guarantee the data confidentiality and security,through adding platform and middleware modules.The security policy was described in the XACML language,and the security and flexibility of the policy were analyzed.